Readiness for pericardiocentesis in cardiac tamponade: A case report - Odu C; Uwanuruochi K (Ibom Medical Journal, 2024)
Mortality is preventable in cardiac tamponade. We report a 23-year old woman with massive pericardial effusion who had an adverse outcome. We discuss measures which if followed will improve outcome in emergency pericardiocentesis.